Women of letters and arts in the south of Colombia. 1930-1950 (2019)
This paper aims at visibilizing a group of women in the south of Colombia in the 1930s and 1940s, mostly teachers, who were poets and musical composers, breaking with models of femininity preached by the conservative hegemony. The Liberal Republic promoted new political and cultural spaces, and the sociability network that arose between these intellectuals and the writers and musicians of the time helped these women artists to overcome geographical isolation and disseminate their artwork in the region and the country. Propopograpic analysis was used to study this collective, leading to the identification of group characteristics, as well as individual peculiarities. It was found that family environments connected with intellectual or artistic life favored the development of this collective, as well as sociability networks, which promoted new experiences with writing and artistic work for these women.